COVID-19 and Youth Psychopathological Distress in Umbria, Central Italy: A 2-Year Observational Study in a Real-World Setting - Menculini, Giulia; Pomili, Giorgio; Brufani, Francesca; Minuti, Agnese; Mancini, Niccolò; D’Angelo, Martina; Biscontini, Sonia; Mancini, Enrico; Savini, Andrea; Orsolini, Laura; Volpe, Umberto; Tortorella, Alfonso; et al. (Frontiers in Psychiatry, 2022)
Introduction Adolescents and young adults represent a vulnerable population in the context of the Coronavirus disease 2019 (COVID-19) pandemic. The present retrospective study aims to investigate the pandemic’s psychological impact on adolescents and young adults by analyzing data from an outpatient mental health service dedicated to youths in Umbria, central Italy. Materials and Methods The clinical charts of subjects aged 14–24 who first accessed the service in the timeframe between March 1st, 2019, and February 28th, 2021, were reviewed. Subjects were divided into two subgroups according to the period of time when they accessed the service (pre-COVID-19 vs. during- COVID-19 outbreak). Bivariate analyses were performed using the Chi-square test and the Welch’s t-test. A secondary analysis was performed considering only subjects suffering from psychiatric disorders. Furthermore, data concerning individuals who were already followed by the service before the pandemic were analyzed by the McNemar’s test and the t-paired test to assess changes in treatment features. Results The number of new accesses during the pandemic period remained stable. After the emergency onset, youths accessing the service showed a higher prevalence of anxiety disorders (p = 0.022). During the COVID-19 period, services were more frequently delivered by using a digital mental health approach (p = 0.001). Psychopharmacological treatment was more frequently prescribed among subjects that were referred to the service after the pandemic onset (p = 0.033). As for substance use, a highly significant reduction in opioid use was observed (p = 0.003). Family therapy was delivered less frequently in the during-COVID-19 subgroup, especially in the subpopulation of subjects suffering from psychiatric disorders (p = 0.013). When considering subjects referred to the service in the pre-COVID-19 period, the number of interventions provided to this population increased after the pandemic outbreak (p = 0.038). Conclusion In the context of the COVID-19-related public health crisis, youths represent an at-risk population for which pathways to care should be reinforced, and targeted interventions, including psychosocial treatments, should be implemented.